Pengaruh Tepung Kiambang (Salvinia molesta) Terfermentasi dalam Ransum terhadap Karkas Itik Peking (Anas platyrhynchos domesticus) - N N E Sulistyawati; Nurhayati; I Panjaitan (PETERPAN (Jurnal Peternakan Terapan), 2020)
This study aims to analyze the use of fermented kiambang flour (Salvinia molesta) on rations against the quantity of peking duck carcasses. This research was conducted in the livestock cage of Lampung State Polytechnic. The research method carried out is a descriptive method. Data collection is done by taking samples from controls and treatment with a total of 15 ducks each at the end of maintenance. The result the treatment given in addition to 15% fermented kiambang flour in rations produces carcass weight (714.26 g), carcass percentage (52.49%), chest percentage (29.08%), thigh percentage (26.37 %), winged percentage (16.92 %) and abdominal fat percentage (0.77 %). Addition 15% fermented kiambang flour not affect to carcass weight, carcass percentage, chest percentage, winged percentage, and abdominal fat percentage.